Christian Mindfulness and Mental Health: Coping through Sacred Traditions and Embodied Awareness - Veronica L. Timbers; Jennifer C. Hollenberger (Religions, 2022)
Mindfulness is increasingly implemented as a tool in mental health practice for coping and self-care. Some Christians worry that these practices might be in conflict with their own tradition, while other Christian contexts are reclaiming the contemplative aspects of the faith. Though clinicians are not trained to teach on religious topics and ethically must avoid pushing religion onto clients, conceptualization and research extend the benefits of mindfulness practices for religious clients. This paper will discuss the evidence for using mindfulness in mental health treatment and connect mindfulness to the Christian tradition. The authors explore how intentional awareness and embodiment of the present moment are supported in Christian theology through the incarnation of Jesus and God’s attention of the physical body in the Christian scriptures. The authors also discuss how sacraments and prayer naturally overlap with mindfulness practices for the dual purposes of emotional healing and spiritual growth. To bolster the benefits of mindfulness in the psychological and religious realms, the purpose of this paper is to empower therapists to address client concerns of whether mindfulness is in conflict with Christianity, support clients in expanding current Christian religious coping, and provide Christian leaders with more information about how mindfulness elements are already present in Christian rituals and beliefs.